Gastrointestinal adverse events associated with immune checkpoint inhibitor therapy. (17th December 2019) - Rajha, Eva; Chaftari, Patrick; Kamal, Mona; Maamari, Julian; Chaftari, Christopher; Yeung, Sai-Ching Jim
Abstract: Immunotherapy with checkpoint inhibitors has revolutionized cancer therapy and is now the standard treatment for several different types of cancer, supported by favorable outcomes and good tolerance. However, it is linked to multiple immune manifestations, referred to as immune-related adverse events (irAEs). These adverse events frequently affect the skin, colon, endocrine glands, lungs, and liver. The gastrointestinal system is one of the most commonly affected organ systems and is responsible for the most frequent emergency visits resulting from irAEs. However, because immune checkpoint inhibitors are a recent addition to our arsenal of cancer drugs, many health-care providers remain unfamiliar with the management of irAEs. Gastroenterologists involved in the treatment of oncology patients who have received checkpoint inhibitors are currently encountering cases of abdominal pain, diarrhea, and other nonspecific symptoms that may be challenging to manage. This article reviews the gastrointestinal, hepatic, and pancreatic toxicities of checkpoint inhibitors and provides an approach to their diagnosis and recommended workup. It also highlights the management of irAEs according to their toxicity grading and specifically discusses the instances in which corticosteroids should be administered and/or the immune checkpoint inhibitors should be withheld.